1988
DOI: 10.1067/mva.1988.avs0080501
|View full text |Cite
|
Sign up to set email alerts
|

Cervical vessel injury after blunt trauma

Abstract: Blunt trauma accounts for 3% to 10% of cervical vessel injuries. Death and severe neurologic impairment have been reported in more than 80% of blunt carotid injuries. In our recent experience, 10 patients sustained 18 blunt cervical arterial injuries: two internal carotid artery (ICA) dissections, three ICA transections with pseudoaneurysm, five ICA thromboses, two vertebral artery dissections, one vertebral artery transection with pseudoaneurysm, one vertebral artery thrombosis, one minimal vertebral artery i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…Theoretically, timely treatment may prevent progression to frank dissection, formation of a pseudoaneurysm, or thrombosis, thus avoiding secondary neurologic deficits. Accordingly, several reports have shown that outcome correlates with neurological status at diagnosis [4, 12, 13, 14, 15]. A variety of clinical signs and symptoms should raise suspicion for BCI, including: direct evidence of lateral neck trauma, ipsilateral Horner syndrome from injury to nearby sympathetic nerves, transient ischemic attacks, lucid intervals followed by neurologic deterioration, and any focal deficit unexplained by computed tomographic scans of the head or detected spine trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, timely treatment may prevent progression to frank dissection, formation of a pseudoaneurysm, or thrombosis, thus avoiding secondary neurologic deficits. Accordingly, several reports have shown that outcome correlates with neurological status at diagnosis [4, 12, 13, 14, 15]. A variety of clinical signs and symptoms should raise suspicion for BCI, including: direct evidence of lateral neck trauma, ipsilateral Horner syndrome from injury to nearby sympathetic nerves, transient ischemic attacks, lucid intervals followed by neurologic deterioration, and any focal deficit unexplained by computed tomographic scans of the head or detected spine trauma.…”
Section: Discussionmentioning
confidence: 99%
“…15 Following initiation of a screening programme for blunt carotid and vertebral artery injuries, 4 Biffl et al found that their incidence of blunt cervical vessel injuries increased from 0.1 to 1.1% of all blunt trauma admission. This series did not separate clearly carotid and vertebral artery injuries, however in a multivariate analysis of their findings, the only independent predictor of blunt vertebral artery injury was cervical spine fracture.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of this type of vascular finding is unknown and it Vertebral artery injuries have been reported previously in the literature. 7,8,13,15,[17][18][19][20][21][22]31,36,38,43 The vertebral arteries originate from the subclavian arteries and enter the foramen transversarium at the level of the sixth cervical vertebra. It leaves the foramen transversarium at the second cervical vertebra and ascends superiorly to merge with the contralateral vessel and form the basilar artery.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of blunt carotid injury is reported to be around one to two per 1000 blunt injuries and accounts for only 1.5-10% of all reported carotid injuries (2)(3)(4)(5)(6). These injuries can be devastating, with mortality rates reported between 20% and 40%, and permanent neurological disabilities occurring in 40 -80% of survivors (4,7,8). One of the recurrent issues with CD is that the patient often does not present or the diagnosis is not entertained until there are neurological deficits present.…”
Section: Introductionmentioning
confidence: 99%